2016
DOI: 10.1161/jaha.116.004438
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Long‐Term Clinical Impact of Acute Stent Malapposition: An Assessment of Dual Antiplatelet Therapy With Drug‐Eluting Stents (ADAPT‐DES) Intravascular Ultrasound Substudy

Abstract: BackgroundThe impact of acute stent malapposition (ASM) on long‐term clinical outcomes in patients undergoing percutaneous coronary intervention is still controversial. We sought to evaluate predictors and long‐term clinical outcomes of ASM.Methods and Results ADAPT‐DES (Assessment of Dual Antiplatelet Therapy With Drug‐Eluting Stents) was a prospective multicenter study of 8663 patients undergoing percutaneous coronary intervention using drug‐eluting stents. In a prespecified intravascular ultrasound–guided s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 34 publications
1
22
0
1
Order By: Relevance
“…The IVUS study by Wang et al 6) included 2,072 patients with 2,446 lesions from ADAPT-DES (Assessment of Dual Antiplatelet Therapy With Drug-Eluting Stents) study which was a prospective, multicenter registry designed to assess the relationship between platelet reactivity and other clinical and procedural variables vs subsequent stent thrombosis (ST) and adverse clinical events in patients successfully treated with drug-eluting stent (DES). At 2-year follow-up, there was no significant difference in the incidence of cardiac death; myocardial infarction; early, late, or very late ST; or clinically driven target lesion revascularization in patients with ASM vs those without ASM.…”
Section: Acute Stent Malappositionmentioning
confidence: 99%
“…The IVUS study by Wang et al 6) included 2,072 patients with 2,446 lesions from ADAPT-DES (Assessment of Dual Antiplatelet Therapy With Drug-Eluting Stents) study which was a prospective, multicenter registry designed to assess the relationship between platelet reactivity and other clinical and procedural variables vs subsequent stent thrombosis (ST) and adverse clinical events in patients successfully treated with drug-eluting stent (DES). At 2-year follow-up, there was no significant difference in the incidence of cardiac death; myocardial infarction; early, late, or very late ST; or clinically driven target lesion revascularization in patients with ASM vs those without ASM.…”
Section: Acute Stent Malappositionmentioning
confidence: 99%
“…Клиническое значение малаппозиции недостаточно изучено. В нескольких исследованиях указано, что наличие малаппозиции после установки стентов с лекарственным покрытием не было ассоциировано с неблагоприятными событиями в длительном периоде наблюдения [16][17][18]. В то же время есть данные о связи неполной установки стента и тромбоза стента [7,19].…”
Section: оригинальные исследованияunclassified
“…Also, optimal apposition often cannot be achieved in calcified lesions, which might lead to diminished tissue concentration of the antiproliferative drugs. [33][34][35] A current meta-analysis showed that the frequency of stent mal-apposition detected by optical coherence tomography may be lower in patients implanted with G2-DES 35 because these stents are thinner and more flexible than G1-DES. However, the magnitude of the effect of G2-DES relative to G1-DES for TLR and the secondary composite endpoints was not different between calcified and non-calcified lesions.…”
Section: Baseline Characteristics: Non-calc Vs Calcmentioning
confidence: 99%
“…7,8 Also, the extent of mal-apposition may not be related to DES restenosis, because a previous report suggested that the incidence of clinical events was low and similar regardless of stent mal-apposition detected by optimal coherence tomography and/or intravascular ultrasound. 33,34 Alternatively, the extent of mal-apposition may be different between G1-DES and G2-DES in non-calcified lesions, but not in calcified lesions.…”
Section: Baseline Characteristics: Non-calc Vs Calcmentioning
confidence: 99%